Management of Discrimination and Its Relationship to Job Satisfaction among Principals of Junior High Schools - Abdul Hussein, Hussein Allawi (Journal of Tikrit University for Humanities, 2020)
The objective of the current research is to identify the management of excellence and job satisfaction among principals of non-academic schools, and to identify the correlation between them. The research sample consisted of 30 director and director of preparatory schools distributed in three areas are the center and the center and remote in the breeding of Baghdad Rusafa the third academic year 2018-2019 adopted a researcher on the scale for measuring the circuit of excellence and scale have been verified the validity and reliability of both instruments. The researcher relied on descriptive approach appropriate to the variables of research, and used the researcher in the analysis of research data statistical analysis Program Spss For human and social sciences and reached the following results: 1- Principals have good discrimination management and are seeking to own all areas. 2 - Principals of high schools have a high level of job satisfaction. 3 - There is a strong relationship between the administration of discrimination and job satisfaction in the principals of junior high schools, the more the principal of the school has a functional satisfaction from the tasks entrusted to him is seeking to have a distinct management.